With (Great) Power Comes (Great) Responsibility: A Move Toward Greater Responsibility for States Exercising Power Abroad (Al-Jedda v the United Kingdom) - Henderson, Laura (Utrecht Journal of International and European Law, 2012)
This case note addresses the recent European Court of Human Rights case Al-Jedda v the United Kingdom. In this case, the Court decided that the act of detaining and interning the applicant in Iraq was attributable to the United Kingdom, and not the United Nations, and that the applicant fell under the UK's jurisdiction. Having established jurisdiction, the Court addressed whether Al-Jedda's internment violated Article 5(1) of the European Convention on Human Rights. In order to answer this, the Court had to decide whether Article 103 of the UN Charter, together with a UN Security Council Resolution authorizing the UK (among other States) to secure and maintain security in Iraq, entailed a conflict of norms that resulted in the inapplicability of the ECHR's right to liberty. The Court concluded that no such conflict was present and, thus, that the UK had violated the right to liberty.